Social Values Reflected in "Batu Dara Muning" An Oral Literature of Dayak Keninjal Tribe - Martono Martono (JETL (Journal of Education, Teaching and Learning), 2018)
Oral literature has an important function in life because it can reflect people's lives and instil a sense of love for their own culture. Oral literature is a cultural heritage of the region passed down from generation to generation which is narrated from mouth to mouth and has a noble value. The noble value contained in oral literature reflects the local culture of the tribe. Certain noble values must be continuously preserved and implemented in the life of society and state. The noble value as a form of character education, such as social values. Therefore, positive social values must be maintained. The social values as many ancestral riches are also found in Dayak Keninjal oral literature titled Batu Dara Muning. The social value that can be found in oral literature entitled Batu Dara Muning is the value of a mother's love for a child, obedient to parents, forbidden marriage, obedience to customs. To analyze oral literature Batu Dara Muning used an approach of a sociology of literature. The reason literature is a mirror of the lives of the people who own the story. Stories or events expressed in oral literature are sourced from events in society with the narrator's imagination. The character used in oral literature is not the name of the character in his tribe, but the name made by the narrator.